Synthesis and adsorption behavior of mesoporous alumina and Fe-doped alumina for the removal of dominant arsenic species in contaminated waters. Issue 1 (February 2019) - Inchaurrondo, N.; di Luca, C.; Mori, F.; Pintar, A.; Žerjav, G.; Valiente, M.; Palet, C.
Graphical abstract: Highlights: Mesoporous Al2 O3 and Fe-Al2 O3 were synthesized by a sol-gel methodology. Mesoporous synthesized materials were effective As(III) and As(V) adsorbents. Mesoporous alumina showed better performance than commercial alumina. Well-defined channeled mesostructures avoided pore blockage, facilitating adsorption. Arsenic uptake may occur through ligand exchange and electrostatic interaction. Abstract: Ordered mesoporous Al2 O3 and Fe-Al2 O3 materials were synthesized at room temperature by an easy and environmentally friendly self-assembly sol-gel route, to be tested for arsenic removal. Solid samples were thoroughly characterized by several techniques. Synthetized and commercial alumina samples were evaluated as adsorbents for the removal of dominant arsenic species under a wide pH range (3.6–11.5). The mesoporous alumina showed higher adsorption capacity (90 mg/g As(V), pHeq 4) than commercial alumina (54 mg/g As(V), pHeq 4), due to its amorphous structure, uniform accessible mesopores and higher surface acidity. The Fe bearing material exhibited strong As affinity. As(III) adsorption resulted much lower than for arsenate (maximum uptake of 16 mg/g, at pH 8), since As(III)-adsorbent interaction is only based on weak Van der Waals force. Arsenic isotherms adjusted well to the Freundlich model and more accurately to the three parameters Sip´s model. The kinetics results fitted the Elovich model. As pH increased, adsorption capacity decreased due to the reduction of electrostatic interactions. Under alkaline conditions arsenic desorption was achieved, although the stability of the material was compromised. The presence of several interfering ions was evaluated. Phosphate ions showed the highest interference. The use of a tap water matrix increased As(V) adsorption, encouraging the use of these materials in the treatment of real polluted waters.